The impact of the COVID-19 pandemic and the free vaccination policy on seasonal influenza vaccination uptake among older adults in Ningbo, Eastern China - Lixia Ye; Jieping Chen; Qiuhong Mei; Yexiang Sun; Tianchi Yang (Human Vaccines & Immunotherapeutics)
In 2020–21, during the COVID-19 pandemic, a free influenza vaccination program was initiated among the elderly residents in Ningbo, China. The impact of the COVID-19 pandemic and free vaccination policy on influenza vaccine uptake needs to be evaluated. The influenza vaccine uptake among individuals born before 31 December, 1962 from 2017–18 to 2022–23 season in Ningbo was analyzed. Multivariate logistic regressions were used to estimate the impact of the COVID-19 pandemic and free vaccination policy. Our analysis included an average of 1,856,565 individuals each year. Influenza vaccination coverage increased from 1.14% in 2017–18 to 33.41% in 2022–23. The vaccination coverage among the free policy target population was 50.03% in 2022–23. Multivariate analysis showed that free vaccination policy increased influenza vaccine uptake most (OR = 11.99, 95%CI: 11.87–12.11). The initial phase of the pandemic was associated with a positive effect on influenza vaccination (OR = 2.09, 95%CI: 2.07–2.12), but followed by a negative effect in the subsequent two seasons(2021–22: OR = 0.75, 95%CI: 0.73–0.76; 2022–23: OR = 0.40, 95%CI: 0.39–0.40). COVID-19 vaccination in the current season was a positive predictor of influenza vaccine uptake while not completing booster COVID-19 vaccination before was negative predictor in 2022–23. Having influenza vaccine history and having ILI medical history during the last season were also positive predictors of influenza vaccine uptake. Free vaccination policies have enhanced influenza vaccination coverage among elderly population. The COVID-19 pandemic plays different roles in different seasons. Our study highlights the need for how to implement free vaccination policies targeting vulnerable groups with low vaccination coverage.